Photophysiological and Oxidative Responses of the Symbiotic Estuarine Anemone Anthopleura hermaphroditica to the Impact of UV Radiation and Salinity: Field and Laboratory Approaches - Edgardo Cruces; Víctor M. Cubillos; Eduardo Ramírez-Kushel; Jaime A. Montory; Daniela A. Mardones; Oscar R. Chaparro; Francisco J. Paredes; Ignacio Echeverría-Pérez; Luis P. Salas-Yanquin; Joseline A. Büchner-Miranda (MDPI AG, 2024)
The estuarine anemone Anthopleura hermaphroditica and its symbiont Philozoon anthopleurum are continuously exposed to intense fluctuations in solar radiation and salinity owing to tidal changes. The aim of this study was to evaluate the effects of the tidal cycle, solar radiation, and salinity fluctuations on the photosynthetic and cellular responses (lipid peroxidation, total phenolic compounds, and antioxidant activity) of the symbiont complex over a 24 h period in the Quempillén River Estuary. Additionally, laboratory experiments were conducted to determine the specific photobiological responses to photosynthetically active radiation (PAR), ultraviolet radiation (UVR), and salinity. Our field results showed that the photosynthetic parameters of the symbiont complex decreased with increasing ambient radiation; however, no relationship was observed with changes in salinity. Increased peroxidative damage, total phenolic compound levels, and antioxidant activity were mainly related to increased UVR and, to a lesser extent, PAR. During the dark period, only PAR-exposed organisms returned to the basal levels of photosynthesis and cell damage. Laboratory exposure confirmed the deleterious effects of UVR on the photosynthetic response. The present study suggests that the ability of A. hermaphroditica to acclimate to natural radiation stress is mediated by the concerted action of various physiological mechanisms that occur at different times of the day, under varying levels of environmental stress.